STEM Learning in Higher Education: A Comparative Study of Science Curriculum in Singapore and Indonesia - Siti Fatimah; Ani Rusiolwati; Edy Cahyono; Rokhmaniyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to compare STEM education in higher education institutions in Indonesia and Singapore. This research is a systematic literature review with a PRISMA approach. Document searches were conducted using the PoP application in the Google Scholar database. Documents were analyzed from 2020-2024, resulting in 500 documents from the Google Scholar database. Further analysis based on research focus yielded 40 relevant documents. The analysis results show that STEM education in higher education institutions in Indonesia and Singapore has similarities and differences in terms of objectives, aspects, and implementation. The goal of STEM education is directed towards enhancing individual skills to face challenges and meet the demands of the workforce related to 21st-century skills. STEM education in Singapore and Indonesia includes similar aspects, such as support from government and non-government institutions, teaching aspects related to the integration of teaching with other learning models/techniques, efficacy aspects in terms of educators' confidence in their ability to implement STEM, and material aspects concerning the availability of facilities that support learning. The implementation of STEM education in Singapore and Indonesia has been optimally carried out by educators and students through clear learning frameworks and the integration of courses with STEM